THE CONDITION OF DEVELOPMENT OF LEXICAL COMPETENCE USING AUTHENTIC MATERIALS IN TEACHING ENGLISH IN NON-PHILOLOGICAL EDUCATIONAL INSTITUTIONS - Kholiyorov, Bunyod (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article represents the current state of teaching English for Specific Purposes (ESP) using authentic materials. The importance of teaching the English language in non-philological institutions approaches to material selection, design, and implementation mainly focused on supporting ideas.